The implementation of Electronic Spreadsheets in the initial formation of the Chemistry Teacher: Perspectives and difficulties - Silva , Francisco Francivaldo de Souza; Neves, Thiago Goncalves das (Seven Editora, 2023)
The Electronic Spreadsheet is a powerful digital spreadsheet that has several tools for the treatment, analysis, simulation and sharing of data. All this functionality makes it an excellent resource to use in the classroom. For this, this resource must be included and experienced in the initial training of the teacher. Thus, the present work aims to analyze the first experience of a Chemistry Degree class using electronic spreadsheets for experimental data processing in Physical Chemistry classes. For data collection, a questionnaire was used, based on a qualitative approach, about the perspective and difficulties faced by the students in this first experience. The results indicate that there is a mutual recognition of the class that the Electronic Spreadsheet is a very useful tool that allows the resolution of calculations faster, optimizing a considerable time compared to manual calculations, in addition to facilitating the construction and analysis of tables and graphs, means of representation of data widely used that enable the use of regression analysis,  a technique that allows verifying the existence of a relationship between a dependent variable and one or more independent variables. Still, much of the class found it difficult to use the tool because it was their first experience. It is clear that the implementation of technology in education brings great benefits in the process of teaching learning, but that for this, it is necessary to have security in its application, since the new technologies bring with them a certain degree of complexity. The Electronic Spreadsheet, being one of these technologies, should be implemented in the initial training of the teacher so that the future teacher obtains mastery and can enjoy its functionality in the exercise of his profession. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-040